Mild steel protection with tannic and polyaspartic acid in cooling systems. Issue 5 (2nd September 2019) - Sezer, Esma; Öztürk, İpek
Abstract : Purpose: Tannic acid (TA) is one of the green corrosion inhibitors for mild steel; its anti-corrosive performance in alkaline water on mild steel when it is used together with polyaspartic acid (PASA) still has not been investigated. The purpose of this study is to develop an effective, biodegradable and environment-friendly novel corrosion inhibitor based on TA and PASA as an alternative to the conventional inorganic inhibitors for mild steel in decarbonised water, which is common in cooling systems. Design/methodology/approach: Corrosion inhibition mechanism is investigated by electrochemical techniques such as polarisation measurements and electrochemical impedance spectroscopy, and results were evaluated to determine the optimum inhibitor concentration for industrial applications. Additionally, practice-like conditions are carried out in pilot plant studies to simulate the conditions in cooling systems. Thus, the efficiencies of the inhibitors are evaluated through both weight loss and linear polarisation resistance measurements. Moreover, the corrosion product is characterised by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) and Fourier-transform infrared spectroscopy (FTIR) analysis. Findings: TA shows high inhibition efficiency especially towards pitting corrosion for mild steel in decarbonised water. PASA addition in the cooling systems improves the inhibition efficiency of TA, and at lower concentrations of TA + PASA, it is possible to obtained better inhibition efficiency than TA alone at higher inhibitor amounts, which is essential in economic and environmental aspect. Originality/value: A blended inhibitor program including TA and PASA with suggested concentrations in this work can be used as an environmental friendly treatment concept for the mild steel corrosion inhibition at cooling systems.